L’edizione Einaudi del Capitale e il rapporto Hegel-Marx - Alessandroni, Emiliano (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2026)
The following contribution aims to highlight certain lexical choices that have characterized the new Italian translation of Marx's Capital (Volume I). Choices that appropriately reflect the linguistic and conceptual heritage that this work has received from Hegel's thought. The team of translators who worked for Einaudi sought to pay particular attention to such heritage, though the adopted solutions do not always seem to have adequately captured it. Following the path they traced, some alternative solutions have therefore been proposed. Particular focus has been given to the terms Veräußerung and Entäußerung, and – also taking into account the master-slave dialectic in the “Phenomenology of Spirit”, where the slave performs an eminently material labor – some reflections have been developed regarding the term Arbeiter. Finally, it has been highlighted how Marx's vision of the whole (des Ganzes) preserved his historical materialism from the lapses into economism that characterized nineteenth-century debates on slavery. These aspects we believe may also offer new stimuli to understand more deeply the philosophical value of Capital. Hegel; Capital; Arbeiter; Surplus Value; Dialectical Movement.